Tantra vision : an invitation to silence - Osho. (New Delhi : Fusion Books, 2009)
Book Summary of Tantra Vision An Invitation To Silence Silence means a state of inner peace, and a state of joy without any inner turmoil Our mystic Osho identifies joy as an outcome of love, where conflict is transformed into harmony. Love between man & woman through sex in a well known worldly relationship. But to have joy through sex while the conflict between masculinity and femininity is completely vanished is rather beyond normal concept. Osho in this book takes its reader to realize such situation and achieve the joy without conflict, leading to silence. This book of Osho is an wonderful experience to go through for a reader keen to achieve the superior Values.
Keywords: Spiritual life; Guenther, Herbert V. -- Royal Song of Saraha